Transnational production of Taiwanese integrated circuit industry in China - Chang, Chiung-Wen (2010)
The trajectory of the Taiwanese economy over past decades has reflected transitions in global geo-economy towards a vertical specialisation of global trade, knowledge-based competition, variation of industrialisation in the Third World, regional trisection of the world economy, etc. Its industry, making remarkable progress based on a long-term national assistance, is involved in the outward direct investment whereby overseas production is arranged. Such strategic actions of industrial capital slice through national boundaries and, meanwhile, incorporate state-business relationships on a broader scale at a national level. The thesis seeks to portray the transnationalisation of the Taiwanese IC sector through its specific organisational processes and spatial dynamics with an aim to understanding the way that indigenous firms are associated with the home state and the convergence of IC production systems on subnational, transnational and global scales. This work finds that the outward expansion of the IC industrial capital reflects a spatial trend converging on China, the Yangtze River Delta in particular, owing to a reshuffle of the global electronic production chain. However, flow of capital and material along the chain across the Taiwan Strait move along a circuitous route. It also finds that a persistent inter-state feud accounts for the domestic debates over the westward investment of the IC capital. There is tension between the neo-liberalist logic of business practices and national intervention in a guided capitalist stance. It underlines the conflicts of imperative territoriality. On the one hand, the firms recognise the necessity of stretching industrial territories to the Mainland in consideration of sectoral competitiveness. On the other hand, what the state is concerned with lies not only in the impacts of industrial de-territorialisation upon domestic industries but also in the result of over-dependence upon China that would incorporate national economy into economic territories of the Great China Circle.